2018
DOI: 10.1177/1545968318807054
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Cueing Treatment of Neglect in Stroke Patients Leads to Improvements in Activities of Daily Living: A Randomized Controlled, Crossover Trial

Abstract: Background. Visuospatial neglect is a disabling syndrome with serious consequences for activities in daily life. This study investigated the effect of adaptive cueing during a reading task as a possible treatment for neglect by including (1) a task relevant for the patient's daily life, (2) a fading out procedure to stimulate independent orientation to the left by selfcueing, and (3) a clear definition of neglect severity for the adaptive treatment protocol. Methods. A randomized controlled crossover design wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 32 publications
(50 reference statements)
0
14
0
3
Order By: Relevance
“…Neglect kann weder als Syndrom noch in seinem Schweregrad unabhängig von einer wissenschaftlichen Konstruktion der Umgebung defi niert werden, in der die Patient_innen agieren. Umso klarer ist, dass auch seine Behandlung eine kognitive Theorie der visuellen Suche umfassen muss (siehe Ten Turgut et al, 2018).…”
Section: Ohne Ein Wissenschaftliches Verständnis Des Relativen Schweregrades Keine Therapieunclassified
See 1 more Smart Citation
“…Neglect kann weder als Syndrom noch in seinem Schweregrad unabhängig von einer wissenschaftlichen Konstruktion der Umgebung defi niert werden, in der die Patient_innen agieren. Umso klarer ist, dass auch seine Behandlung eine kognitive Theorie der visuellen Suche umfassen muss (siehe Ten Turgut et al, 2018).…”
Section: Ohne Ein Wissenschaftliches Verständnis Des Relativen Schweregrades Keine Therapieunclassified
“…Ganz ähnlich ging die neuropsychologische Therapie des Neglects in der Studie von Turgut et al (2018) vonstatten. Für die verschiedenen Schweregrade des Neglects wurden verschiedene geschützte kognitive Umgebungen defi niert, deren Bewältigung den Patient_innen gerade noch möglich war.…”
Section: Das Ziel Neuropsychologischer Therapie Ist Das Systematische Verschwinden Der Therapeutin Oder Des Therapeutenunclassified
“…For USN, effective intervention methods such as prism adaptation (Eramudugolla, 2010;Goedert et al, 2020), visual scanning training (Van Kessel et al, 2013Weinberg et al, 1977), trunk rotation (Wiart et al, 1997), and limb activation (Eskes et al, 2003;Robertson & North, 1992) have been reported; however, these trainings are considered voluntary exploratory trainings based on the concept of goal-oriented attention. In this regard, Turgut et al (2018) recommended a reading training that combined an exogenous cue based on stimulus-driven attention, in addition to the endogenous cue based on goal-directed attention for patients with USN. They showed that the Catherine Bergego Scale (CBS), which measures the behavioural outcome for USN, improved in the intervention group compared to the control group.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, stimulus-driven attentional function-based treatment may be effective in improving behavioural outcome for patients with USN. However, this training was performed primarily in a sitting position (Turgut et al, 2018), which is difficult to apply during walking.…”
Section: Introductionmentioning
confidence: 99%
“…It is a new, highend way of human-computer interaction. The complete BCI system includes four parts: signal acquisition part, the feature extraction part, pattern recognition part, and control command output part (Turgut et al, 2018). The brain's thinking activity mainly depends on the central nervous system.…”
Section: Introductionmentioning
confidence: 99%